2022
DOI: 10.2196/38826
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing How Providers Assess the Appropriateness of Video Visits: Interview Study With Primary and Specialty Health Care Providers

Abstract: Background The rapid implementation of virtual care (ie, telephone or video-based clinic appointments) during the COVID-19 pandemic resulted in many providers offering virtual care with little or no formal training and without clinical guidelines and tools to assist with decision-making. As new guidelines for virtual care provision take shape, it is critical that they are informed by an in-depth understanding of how providers make decisions about virtual care in their clinical practices. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…This suggests the modality was not clinically suitable for certain patients. While determining patient suitability for different virtual care innovations is a complex process [26, 35,50] the re nement of guidelines for clinicians concerning patient suitability for various virtual care modalities may encourage proper implementation in primary healthcare while improving clinical outcomes and patient experience [51]. In a primary mental health care setting where clinicians considered the clinical appropriateness of patients for participation in a virtually administered mental health care program, clinical risk was averted, and implementation facilitated [13], demonstrating that having a benchmark to ascertain patient compatibility with virtual care may be bene cial.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests the modality was not clinically suitable for certain patients. While determining patient suitability for different virtual care innovations is a complex process [26, 35,50] the re nement of guidelines for clinicians concerning patient suitability for various virtual care modalities may encourage proper implementation in primary healthcare while improving clinical outcomes and patient experience [51]. In a primary mental health care setting where clinicians considered the clinical appropriateness of patients for participation in a virtually administered mental health care program, clinical risk was averted, and implementation facilitated [13], demonstrating that having a benchmark to ascertain patient compatibility with virtual care may be bene cial.…”
Section: Discussionmentioning
confidence: 99%
“…We used a combination of administrative data and provider referrals to purposefully sample 28 providers [ 29 ], ranging in specialties from primary care (n=11), cardiology (n=7), palliative care (n=5), and spinal cord injury (n=5). These specialties were identified to represent a diverse set of clinical care and services that can be offered during a video visit [ 30 ]. Primary care addresses a patient’s medical, social, and behavioral needs through history-taking, physical examinations, laboratories, imaging, and medication management [ 31 ]; cardiology care focuses on a patient’s cardiac conditions and offers specialized procedures [ 32 ]; palliative care typically centers around in-depth goals of care discussions and medication management near the end of life [ 33 ]; and spinal cord injury care provides comprehensive education, counseling, coordination, and ongoing monitoring for a highly complex chronic condition [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…International studies have primarily investigated video consultation in the context of general practitioners (GP), ambulatories, and hospitals, and prior findings in terms of effectiveness and accessibility to care are largely positive although technological challenges are continuously highlighted [ 3 5 ]. Successful use depends on patients’ and clinicians’ willingness and acceptance towards new technologies, technological training and support as well as patients’ specific medical conditions [ 2 – 4 , 6 ]. Clinicians appreciate greater flexibility and saved time for their patients.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is crucial for specialists to have optimal conditions for their medical practice in their clinical encounter. Studies exploring the use of video consultation in medical specialists’ practice have shown that the use of video consultation for patients with chronic diseases [ 6 ] and in follow-up consultations [ 10 ] can be appropriate. Within psychiatry, a review showed that video consultation for elderly patients with depression worked well [ 11 ], while another study based on the perspective of psychiatrists highlighted that handling certain topics such as traumatic incidents was not appropriate by video [ 12 ].…”
Section: Introductionmentioning
confidence: 99%